2008
DOI: 10.1177/1362361308091652
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between measures of self-esteem and psychological adjustment among adolescents with Asperger Syndrome

Abstract: This exploratory study examines the relationships between self-esteem and psychological adjustment among 19 adolescents with Asperger syndrome and 19 typically developing adolescents using a model developed by Harter. The groups were matched for age (mean 13 years), sex (M:F 16:3) and ethnicity (white British). Participants completed four quantitative measures examining self-competencies, social approval, anxiety, depression and self-worth. Findings revealed significant group differences: the adolescents with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
51
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 13 publications
10
51
1
1
Order By: Relevance
“…Kuusikko et al (2008) found that children and adolescents with high functioning autism/AS report significantly more social anxiety symptoms than do their TD peers, and that these symptoms increase as individuals get older, in contrast to the pattern in TD peers. Additionally, Williamson et al (2008) found that adolescents with AS perceive themselves to hold lower peer approval than TD controls, while placing the same emphasis on its importance. However, studies to date have not compared ASC and TD adolescent reactions to ostracism in an experimental setting, nor have they looked at these reactions in terms of well-validated models of ostracism.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Kuusikko et al (2008) found that children and adolescents with high functioning autism/AS report significantly more social anxiety symptoms than do their TD peers, and that these symptoms increase as individuals get older, in contrast to the pattern in TD peers. Additionally, Williamson et al (2008) found that adolescents with AS perceive themselves to hold lower peer approval than TD controls, while placing the same emphasis on its importance. However, studies to date have not compared ASC and TD adolescent reactions to ostracism in an experimental setting, nor have they looked at these reactions in terms of well-validated models of ostracism.…”
Section: Introductionmentioning
confidence: 94%
“…Although individuals with ASC can lack insight into their own mental states and emotions (e.g. Hill et al 2004), several recent studies have shown that selfreport can be a useful methodology for this group when reporting on their everyday experience (Baron-Cohen et al 2001;Berthoz and Hill 2005;Chalfant et al 2007;Hedley and Young 2006;Kim et al 2000;Kuusikko et al 2008;Williamson et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Being different, however, is often not accepted by typical adolescents (Humphrey & Lewis, 2008;Martino & Pallotta-Chiarolli, 2005), therefore these results may have implications for inclusion practices by challenging what most typical adolescents consider "normal". Given the high rates of bullying in autism (Roekel, Scholte, & Didden, 2010), with autistic adolescents reporting that encounters with peers can be frequently hostile or negative (Carrington et al, 2003b;Williamson, Craig & Slinger, 2008), teaching typical children the positives of diversity (and neurodiversity) could be one way of improving autism acceptance. Finally, this study demonstrates the importance of enabling young people on the autistic spectrum to speak out about their social experiences, in this instance by revealing new insights into reputation concerns in autism.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Williamson, Craig, and Slinger (2008) reported that individuals with ASD perceive themselves as being socially incompetent, and received more negative feedback and less peer approval. This awareness of social difficulties and sense of aloneness may contribute to social anxiety evidenced in ASD (Kuusikko et al, 2008).…”
Section: Research-article2015mentioning
confidence: 99%